2012
DOI: 10.1186/1472-6963-12-435
|View full text |Cite
|
Sign up to set email alerts
|

Association between unemployment rates and prescription drug utilization in the United States, 2007–2010

Abstract: BackgroundWhile extensive evidence suggests that the economic recession has had far reaching effects on many economic sectors, little is known regarding its impact on prescription drug utilization. The purpose of this study is to describe the association between state-level unemployment rates and retail sales of seven therapeutic classes (statins, antidepressants, antipsychotics, angiotensin-converting enzyme [ACE] inhibitors, opiates, phosphodiesterase [PDE] inhibitors and oral contraceptives) in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…Prescriptions more generally rose across the United States during recessionary times (Bradford and Lastrapes, 2013). This finding was corroborated by Kozman et al (2012) who found that a 1% rise in unemployment is associated with a 4% increase in statins and 3% increase PDE inhibitors use. Leopold et al (2014) find that pharmaceutical sale volumes moderately increased in six European countries but declined in two of the countries where the global financial crisis hit hard.…”
supporting
confidence: 73%
“…Prescriptions more generally rose across the United States during recessionary times (Bradford and Lastrapes, 2013). This finding was corroborated by Kozman et al (2012) who found that a 1% rise in unemployment is associated with a 4% increase in statins and 3% increase PDE inhibitors use. Leopold et al (2014) find that pharmaceutical sale volumes moderately increased in six European countries but declined in two of the countries where the global financial crisis hit hard.…”
supporting
confidence: 73%
“…21,25,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] While there is evidence of a decrease in overall alcohol consumption during recessions, 5,53 studies also consistently find an increase in alcohol related traffic accidents 55 (despite an overall decline in deaths from road traffic accidents), binge drinking, 5 and alcohol related hospitalization during economic contractions. 25 In other words, while on average some people reduce their drinking of alcohol, a subpopulation increases its use to potentially dangerous levels, reflecting that the hypotheses above may apply variously to different groups.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 99%
“…Similar patterns were found for tobacco use in a prospective study in Iceland, where the income effects dominated, but when income was not a constraint smoking increased during the recent downturn. 58 Even with prescription medications, a recent study found increases in opiate consumption in states with higher unemployment rates in the US, 47 though other categories of prescription drugs were largely unchanged. There is also a report of an increase in intravenous drug use-related HIV infections in Greece.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 99%
“…These measures tend to shift the cost-burden to those who needed medicines, in a country where out-of-pocket payments already represented an important part of total health care expenditure [8,9]. Concerns arose about the unintended risk of less equitable access to needed medicines and "cost-related non-adherence" [10,11].…”
Section: Introductionmentioning
confidence: 99%